Long-Term Consequences of Major Extremity Trauma: A Pilot Study. (January 2022) - Castillo, Renan C.; Carlini, Anthony R.; Chaffee, Trisha; Bosse, Michael J.; O'Toole, Robert V.; Kleweno, Conor P.; McKinley, Todd O.; Agel, Julie; Higgins, Thomas F.; Morshed, Saam; Staguhn, Elena D.; Aaron, Rachel V.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Summary: Limited data are available on the longer-term physical and psychosocial consequences after major extremity trauma apart from literature on the consequences after major limb amputation. The existing literature suggests that although variations in outcome exist, a significant proportion of service members and civilians sustaining major limb trauma will have less than optimal outcomes or health and rehabilitation needs over their life course. The proposed pilot study will address this gap in current research by locating and consenting METRC participants with the period of 5–7 years postinjury, identifying potential participation barriers and appropriate use of incentives, and conducting the follow-up examination at several data collection sites. The resulting data will inform the primary objective of refining and developing specific hypotheses to determine the design, scope, and feasibility of the main long-term consequences of major extremity trauma. Three METRC enrollment centers will contact past participants to achieve the goal of completing an interview, select patient-reported outcomes, perform a medical record review, and conduct an in-person clinic visit that will consist of a physical examination, blood draw, and x-ray of the study injury area. If successful, it will be possible to design studies to further examine these effects and develop future therapeutic interventions.